2017
DOI: 10.1002/jbt.21999
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lp‐PLA2 G994T gene polymorphism with risk of ischemic stroke in Chinese population

Abstract: The association between lipoprotein-associated phospholipase A2 (Lp-PLA2) G994T gene polymorphism and the risk of ischemic stroke is unclear. The aim of this study is to investigate the influence of Lp-PLA2 G994T genetic variant on the pathogenesis of ischemic stroke in Chinese population. A total of 348 patients with a clinical diagnosis of ischemic stroke and 260 gender-matched control subjects under physical examination were recruited from hospitals and genotyped for G994T gene polymorphism. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Definitely, the present study suggested that high Lp-PLA2 mass levels could possibly be used as a biomarker for ischemic stroke since; it regarded as SR stratification mainly in Chines and general populations. [ 40 ] Findings of our study certainly revealed that statins therapy produced significant reduction in Lp-PLA2 mass levels in statins user patients compared to the nonstatin users in patients with ischemic stroke that correspond with Safarova et al ., study that revealed a significant effect of statins on the reduction of Lp-PLA2 mass levels in patients with progressive atherosclerosis. [ 41 ] On contrast, Otsuka et al .…”
Section: Discussionsupporting
confidence: 88%
“…Definitely, the present study suggested that high Lp-PLA2 mass levels could possibly be used as a biomarker for ischemic stroke since; it regarded as SR stratification mainly in Chines and general populations. [ 40 ] Findings of our study certainly revealed that statins therapy produced significant reduction in Lp-PLA2 mass levels in statins user patients compared to the nonstatin users in patients with ischemic stroke that correspond with Safarova et al ., study that revealed a significant effect of statins on the reduction of Lp-PLA2 mass levels in patients with progressive atherosclerosis. [ 41 ] On contrast, Otsuka et al .…”
Section: Discussionsupporting
confidence: 88%
“… 29 , 30 The Lp-PLA2 G994T gene polymorphism may be an independent risk factor for ischemic stroke in a Chinese population. 31 Higher levels of Lp-PLA2 in the acute phase were associated with an increased short-term risk of recurrence of vascular events. 32 Furthermore, high serum LP-PLA2 levels are associated with the incidence, severity, and recurrence of AIS, which can be used to guide clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, inconsistent results were obtained even for the same ethnic population and disease as well. For example, a case‐control study demonstrated no significant association between the V279F mutation and ischemic stroke in a Chinese population (OR = 0.82, 95% CI: 0.44‐1.24), whereas another genetic study established an increased risk despite using the same study population and disease (OR = 2.51, 95% CI: 1.02‐5.91, P = .037) . In the case of atherosclerosis, a significant inverse association of V279F polymorphism with clinical atherosclerosis was indicated in a recent meta‐analysis (OR = 0.88, 95% CI: 0.81‐0.95, P = .0007), whereas another study did not reveal any significant associations between the V279F genotype and subclinical atherosclerosis using Mendelian randomization analyses .…”
Section: Genetic Variability and Regulation Of Expressionmentioning
confidence: 99%